Ознаки організованості злочинів: вплив на методику розслідування - Проценко, М.В. (Інститут держави і права ім. В.М. Корецького НАН України, 2009)
Статья посвящена влиянию признаков организованности преступлений на методику расследования. Проанализировано особенности предмета доказывания в делах по преступлениям, совершённым организованными группами и влияния на него и на особенности расследования этих преступлений обязательных признаков совершения преступления организованной группой. The article is devoted to influence of signs of good organization of crimes on the method of investigation. The features of the article of proving are analyzed on business on the crimes accomplished by the organized groups and influences on him and on the feature of investigation of these crimes of obligatory signs of commission of crime by the organized group.